2019
DOI: 10.9734/ijpss/2019/v30i230169
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon and Acid Phosphatase Enzyme Activity Response to Phosphate Rock and Organic Inputs in Acidic Soils of Central Highlands of Kenya in Maize

Abstract: Aims: To evaluate the effects of phosphate rock and organic inputs on soil organic carbon and acid phosphatase activity. Study Design: The experiment was laid in Randomized Complete Block Design with seven treatments replicated thrice. Place and Duration of Study: The study was conducted at Kigogo Primary school in Meru South Sub-county, Tharaka Nithi County, Kenya. The experiment ran for two consecutive seasons the short rains of 2017 (October to December) and long rains of 2018 (March through Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…These results are in accord with Sekaran et al (2019) who also found that urease activity was higher where half rate of chemical N (56 kg/ha) was applied. Similarly, Balezentiene andKlimas (2009), andOmenda et al (2019) also established that urease activities increased in soils fertilized with either animal or green manures and decreased where chemical fertilizer was applied. Raju et al (2013) found that combination of chemical fertilizer with organic inputs resulted in 4 to 77% more urease activity in comparison to application of chemical fertilizer alone.…”
Section: Effect Of Soil Fertility Management Practices On the Activities Of Urease Enzymementioning
confidence: 82%
“…These results are in accord with Sekaran et al (2019) who also found that urease activity was higher where half rate of chemical N (56 kg/ha) was applied. Similarly, Balezentiene andKlimas (2009), andOmenda et al (2019) also established that urease activities increased in soils fertilized with either animal or green manures and decreased where chemical fertilizer was applied. Raju et al (2013) found that combination of chemical fertilizer with organic inputs resulted in 4 to 77% more urease activity in comparison to application of chemical fertilizer alone.…”
Section: Effect Of Soil Fertility Management Practices On the Activities Of Urease Enzymementioning
confidence: 82%
“…The use of mineral fertilizers plays a vital role in soil fertility restoration, and better essential nutrients (Zhou et al, 2022). Additionally, organic resources play a crucial role in soil fertility management over inorganic fertilizer in sustainability terms (Omenda et al, 2019). They can improve soil nutrients, physical properties, and water holding capacity contributing to organic matter formation and maintenance (Lazcano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They can improve soil nutrients, physical properties, and water holding capacity contributing to organic matter formation and maintenance (Lazcano et al, 2013). The combined use of manure and mineral fertilizer has also been suggested as one of the effective ways of improving soil fertility in farming systems (Omenda et al, 2019). However, the fertilization recommendations found in the Central African Republic and elsewhere in SSA are at best-educated guesses.…”
Section: Introductionmentioning
confidence: 99%